Comparison of the Combined Shielding Effectiveness Based on Experimental Studies of Overhead Power Lines Magnetic Field 3D Model - Bovdui I.V. (Problems of the Regional Energetics, 2025)
The aim of the work is an experimental study of the efficiency of combined shielding of the magnetic field generated by transmission lines (HVPL) with single-circuit and triangular arrangements of wires and double-circuit transmission lines with a "Barrel" type of wire arrangement using an active shielding system and passive shields made in the form of solid, or multi-loop, shields. To achieve this goal, the structure of combined shields was determined, which consist of a double-loop active shield and solid or multi-loop shields. The developed combined shields provide increased efficiency in reducing the level of industrial frequency (MF) magnetic field. Designing combined shields is reduced to solving vector games in which the cost vector of the game is calculated based on solutions to Maxwell's equations in a quasi-stationary approximation using the COMSOL Multiphysics software package. The most important results are the calculated values of the spatial arrangement coordinates of two compensation windings of the active shielding system and the values of currents and phases in these windings, as well as the parameters of solid and multi-loop passive screens, which made it possible to increase the efficiency of MF shielding inside residential buildings from that generated by single-circuit HVPL with the triangular wire arrangement and double-circuit HVPL with the "Barrel" type conductor arrangement. The significance of the obtained results is that practical recommendations are given for the justified choice of the spatial arrangement of two shielding windings of the robust active shielding system, as well as the parameters of solid and multi-loop passive screens for combined shielding systems of MF generated inside residential buildings by single-circuit HVPL with triangular wire arrangement and double-circuit HVPL with the "Barrel" type conductor arrangement. The possibility of reducing the induction level of the initial MF to the level of sanitary standards is shown.